Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I feel that this is a very stupid question to be asking, but I can't figure it out. I've been trying to figure out the Mobius inversion formula, with pretty much no experience in this direction at all, and ran into the following problem:

So according to the Mobius inversion formula, $$g(n)=\sum_{d|n}f(d) \Longleftrightarrow f(n)=\sum_{d|n}g\left(\frac nd\right)\mu(d)$$. Yes? Since this is an equivalence, it should work both ways. Let's say $g(n)=1$, in that case, plug it into the right-hand formula and find that $f(n)=0$, or at least Wikipedia tells me that $\sum_{d|n}\mu(d)=0$. Problem: when we look at the formula on the left, we see that $g(n)$ is now equal to the sum of a finite number of zeros, even though we defined it as $1$. What stupid mistake am I making here?

share|improve this question
1  
$\sum_{d\mid n} \mu(d) = 0$ for $n > 1$. But $\sum_{d\mid 1} \mu(d) = 1$. –  Daniel Fischer Jul 16 at 21:37
    
Yes, but $n$ is not necessarily $1$, I think; it's the definition of $f(n)$, for $n \in \mathbb N$, so why should $n$ be restricted to $1$? –  Laertes Jul 16 at 21:39
    
But $$f(1) = \sum_{d\mid 1} g\left(\frac{1}{d}\right)\mu(d) = g(1)\mu(1) = g(1) = 1.$$ For $n > 1$, you have $f(n) = 0$. –  Daniel Fischer Jul 16 at 21:40
    
$f(n)$ is a function, it changes depending on $n$. So when $n=1$ you get $1$, only otherwise do you get $0$. –  Adam Hughes Jul 16 at 21:40
    
But $g(n)$ is supposed to be $1$ for all $n$. –  Laertes Jul 16 at 21:43

1 Answer 1

up vote 1 down vote accepted

The point is that

$$\sum_{d\mid n} \mu(d) = \begin{cases} 1 &, n = 1\\ 0 &, n > 1. \end{cases}$$

Thus, for $g \equiv 1$ you have

$$f(n) = \sum_{d\mid n} g\left(\frac{n}{d}\right)\mu(d) = \sum_{d\mid n} \mu(d) = \begin{cases} 1 &, n = 1\\ 0 &, n > 1 \end{cases}$$

and hence

$$g(n) = \sum_{d\mid n} f(d) = f(1) + \sum_{\substack{d\mid n\\ d > 1}} f(d) = f(1) + \sum_{\substack{d\mid n\\ d > 1}} 0 = f(1) = 1,$$

as it should be.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.